City of ice - Yep, Laurence, 1948- (Yep, Laurence, 1948- City trilogy, 2011)
From the islands of Hawaii, Scirye and her loyal companions pursue the villainous Mr. Roland and evil dragon Badik all the way to the city of Nova Hafnia in the icy Arctic Circle, to prevent Roland from obtaining the power to alter the universe.